The summer getaway [compact disc, unabridged] - Mallery, Susan (Harlequin Audio, 2022)
To escape her demanding family, Robyn Caldwell visits her aunt Lillian in Santa Barbara. While spending time with this woman who's like a mother to her, Robyn will see herself, and the people she loves, with more clarity.